ANALISIS PENGARUH RELATIONSHIP MARKETING STRATEGY TOKOPEDIA.COM TERHADAP KEPUASAN PELANGGAN PADA MASA PANDEMI COVID-19 (STUDI KASUS PADA PERGURUAN TINGGI BISNIS EKONOMI DI PROVINSI BANGKA BELITUNG) - Halim, Nicky; Ruben Manullang, Rizal; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2022)
Variables Trust, Commitment, Communication, and Conflict Handling on customer satisfaction during the Covid-19 pandemic in Bangka Belitung Province. The method used in this study is a quantitative method using a questionnaire to 89 respondents with a proportionate stratified random sampling method using Tokopedia.com as an online purchasing medium. The distribution of this questionnaire is carried out online via google form to respondents who are in the scope of STIE IBEK and STIE Pertiba. The data were processed using statistics using the JASP program, namely the f-test, t-test, and determinant coefficient test (R2). The results of the study show that together Trust, Commitment, Communication, and Conflict Handing have a positive and significant effect on customer satisfaction in students of the Bangka Belitung Islands Province, users of Tokopedia.com. Partially, Commitment and Conflict Handling have a significant effect on customer satisfaction, while Trust and Communication have no significant effect on customer satisfaction. The value R Square is 0.486, which means that the variables that can be explained by Trust, Commitment, Communication, and Conflict Handling are 48.6%, while the rest is influenced by other variables not examined in this study of 51.4%.